2011
DOI: 10.1111/j.2044-8341.2011.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Service‐users’ experiences of an early intervention in psychosis service: An interpretative phenomenological analysis

Abstract: Harris, Katy (2010) Service users' experiences of an early intervention in psychosis service: an interpretative phenomenological analysis. DClinPsy thesis, University of Nottingham. Access from the University of Nottingham repository:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 88 publications
(169 reference statements)
6
61
0
Order By: Relevance
“…Three key themes were identified; 'Consistency and Communication', 'Normalising and Validating', and 'Pushing Boundaries'. All themes emphasised the importance of the relationships with either the EIP service staff or fellow SUs, which replicated the findings from previous research into the experience of EIP service users (Lester, et al, 2011;Harris, et al, 2012;Barr, Ormrod, & Dudley, 2015). To the best of the authors' knowledge, this is the first EIP service evaluation to suggest, from the perspective of SUs, the potential value of taking a graded approach to building trust and pushing boundaries through activities and peer support in EIP services.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Three key themes were identified; 'Consistency and Communication', 'Normalising and Validating', and 'Pushing Boundaries'. All themes emphasised the importance of the relationships with either the EIP service staff or fellow SUs, which replicated the findings from previous research into the experience of EIP service users (Lester, et al, 2011;Harris, et al, 2012;Barr, Ormrod, & Dudley, 2015). To the best of the authors' knowledge, this is the first EIP service evaluation to suggest, from the perspective of SUs, the potential value of taking a graded approach to building trust and pushing boundaries through activities and peer support in EIP services.…”
Section: Discussionsupporting
confidence: 72%
“…Participants valued support from their families and appreciated it when the EIP service collaborated with their family. Harris, Collinson, and Das Nair (2012) conducted interviews with eight EIP service users and analysed the results using Interpretvie Phenemonological Analysis (IPA). The authors identified an overall theme of 'personal journey of recovery' and five superordinate themes of stigma, relationships, understanding the experiences, sense of agency, and impact on sense of self.…”
mentioning
confidence: 99%
“…Such methods are frequently used in evaluation research to explain how a program or intervention operates. Harris and colleagues (2012) used qualitative methods to help understand why Early Intervention in Psychosis (EIP) services are effective by exploring the personal experiences of a small sample of services users. Byng et al (2008) used qualitative methods to conduct a process evaluation of a complex intervention for shared care in mental health.…”
Section: Rationale For Using Qualitative Methodsmentioning
confidence: 99%
“…Other methods used in qualitative studies to enhance rigor of analysis include triangulation of viewpoints by purposefully interviewing people in various roles within an organization, peer debriefing and support meetings among research team members, and providing a detailed audit trail during analysis (Harris, Collinson, & das Nair, 2012; Miles & Huberman, 1994; Mendenhall, Kapp, Rand, Robbins, & Stipp, 2013). …”
Section: Characteristics Of Qualitative Methodsmentioning
confidence: 99%
See 1 more Smart Citation